CRITERIA OF THERMAL CLASSIFICATIONS OF LAKES - Skowron, Rajmund (Bulletin of Geography. Physical Geography Series, 2009)
Since the early twentieth century limnological literature has presented numerous classifications of lakes. Most frequently these classifications refer to genetic systematization. In the latter half of the twentieth century new divisions of inland water bodies were introduced with respect to mictic, trophic and thermal properties. These proposals, however, make up a very diverse and scattered material, particularly due to the considered criteria. The author of this article decided to verify opinions and criteria of these systematisations to provide a better understanding of the problem.